THE EFFECTIVENESS OF SCHOOL EDUCATION - FEATURED IMPLICATIONS CONSIDERATIONS - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The main objective of the paper is to argue for a multidimensional character of effectiveness of school education and to discuss a number of factors that influence the outcome of education directly or indirectly. Assessing the effectiveness of school education sheds light on its current problems and indicated directions for future research on innovative approaches to solving such problems.